Case Report: A Rare Presentation of Sigmoid Volvulus During Pregnancy With an Integrative Postoperative Approach - Al-Sattam, Zahraa Muhmmed Jameel; Saleh, Sabah Mahdi; Fadhel, Hussein Alaa-Alden (Scripta Medica, 2025)
Sigmoid volvulus during pregnancy is an extremely rare but potentially life-threatening condition for both the mother and the foetus. Prompt diagnosis and timely surgical intervention are critical for favourable outcomes. Nutritional support and gut motility regulation may also play a supportive role in recovery. A 25-year-old woman, G3P2A0, at 34 weeks of gestation, came to the emergency department with severe abdominal distension and two weeks of constipation. Despite initial conservative treatment, her condition worsened and she required urgent surgical intervention. A multidisciplinary team, including surgeons, obstetricians and anaesthetists, performed a caesarean delivery followed by resection of the perforated sigmoid colon and a Hartmann’s procedure. The patient recovered well with a functioning stoma and her newborn was healthy following neonatal intensive care. Early surgical decision-making proved critical in saving both lives. This case highlights the importance of early recognition and rapid intervention in managing bowel obstruction during pregnancy. A multidisciplinary approach and timely surgical management are essential to ensure the best outcomes.